Problem-Based Learning Assisted by Mobile Pocket Book in Mechanical Wave to Enhances Students' Concepts Mastery and Creativity - Melanie, Tasya Septiana; 'Ardhuha, Jannatin; Taufik, Muhammad; Harjono, Ahmad (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
The research aims to determine the influence of the model problem-based learning assisted by a mobile pocket book mechanical wave to increasse students' concepts mastery and creativity. The type of research is quasi-experimental and uses a nonequivalent control group design with pre-test and post-test. Population at this study included all students of class XI IPA at SMAN 4 Mataram Academic Year 2022/2023. Samples were taken using purposive sampling technique, so that XI IPA 1 is obtained as an experimental class as many 32 people and XI IPA 2 as control class as many 31 people. Results the final test of concepts mastery obtained an average score of 78.70 in the experimental class and control class 68.81. Meanwhile, the results of the final creativity test obtained an average value of 80.79 for the experimental class and 76.02 for the control class. The hypothesis was analyzed using Manova with the help of IBM SPSS 21. Based on the results of the analysis it can be concluded that there is the influence of the problem-based learning model assisted by the mobile pocket book mechanical wave to increasse students' concepts mastery and creativity.